PENGARUH BRAND AMBASSADOR DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK HANASUI - Ni Luh Gede Antri Asih; Ni Luh Wayan Sayang Telagawathi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was designed to reveal the impact of various variables on Hanasui cosmetics purchasing decisions among undergraduate Management students at Ganesha University of Education. The details of this analysis include: (1) the influence of brand ambassadors on purchasing decisions, (2) the influence of product quality on purchasing decisions, and (3) the synergistic influence between brand ambassadors and product quality on purchasing decisions. This study used a causal quantitative approach with undergraduate Management students as participants. In this study, brand ambassadors, product quality, and purchasing decisions were the objects of research. The sampling technique used was purposive sampling with the Ferdinand formula and a sample size of 100 respondents. Data collection was carried out through questionnaires. Data analysis was carried out using multiple linear regression methods with the help of the SPSS program. The results of this study revealed several important findings, namely: (1) brand ambassadors have a positive and significant influence on purchasing decisions, (2) product quality has a positive and significant influence on purchasing decisions, and (3) brand ambassadors and product quality together have a significant influence on purchasing decisions. In the context of undergraduate Management students as consumers, the presence of brand ambassadors who have attractiveness, credibility, and image suitability can increase interest and confidence in making purchases. On the other hand, good product quality, including durability and attractive design, are rational factors that strengthen purchasing decisions. Thus, the combination of promotional strategies through brand ambassadors and superior product quality can drive increased purchasing decisions for Hanasui cosmetics.